Halal Certification Education with Halal Business Actor Statements (Self Declare) at Kelompok UMK Sahabat in Rasau Jaya West Kalimantan - Lestari, Oke Anandika; Komariyati, Komariyati (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to increase the knowledge of MSE in Rasau Jaya, who are members of the â€œKelompok UMK Sahabat (KUS)â€ regarding obtaining halal certification using a halal statement by business actors or Self Declare. The method stages carried out in this activity were identifying KUS profiles, consumer analysis, education, and evaluation. Evaluation was carried out using a questionnaire. The descriptive data obtained was presented in percentage form. The results of this activity showed that 92% of the products produced by KUS were snacks, 78% of KUS consumers stated that halal certification was a determinant in purchasing food products, educational media using brochures was considered to help understand the material provided, and this activity increases knowledge up to 71.43 %. Continuity of activities through assistance in submitting halal certification through the Self Declare was very necessary.